Aider à la réussite scolaire : des détours sans retours ? Peinture et littérature en classe de Français - Marie-Sylvie Claude; Patrick Rayou
To undertake other activities, even in other disciplines, is often advocated in the fight to overcome academic difficulty. We question this belief by testing the practice which aims to facilitate a student's interpretative reading of literature by the manner in which they appreciate and view a painting. Although it's thought that it's possible to enrol students in an activity they would prefer, the return to the central activities of the discipline, of their own accord, is not guaranteed. In questioning this practice, we mobilise sociological and didactic frameworks which are likely, in our opinion, to restore the dimensions of the social context and the relation with the areas of knowledge that guide the digression and return to the discipline. Our analysis is based on a comparison of the students' activity in the arts of painting and literature from a collection of texts written by 350 senior secondary students, of highly mixed social backgrounds, from académie de Créteil. Our analysis shows that students more often accept and understand, through paintings rather than text, the very specific expectations of the French class room: an appreciation of a creative work's greater sense of meaning, rich and plural and concerned with form. Analysis suggests the mobilisation of three registers of academic learning to help teachers be aware of the transformations necessary to the appreciation of a painting and to re-contextualise it for the appreciation of literature.